Comparative susceptibility of Aedes albopictus and Aedes aegypti to dengue virus infection after feeding on blood of viremic humans: Implications for public health - Whitehorn, J; Kien, D; Nguyen, N; Nguyen, H; Kyrylos, P; Carrington, L; Tran, C; Quyen, N; Thi, L; Le Thi, D; Truong, N; Luong, T; et al. (Oxford University Press, 2015)
Aedes albopictus is secondary to Aedes aegypti as a vector of dengue viruses (DENVs) in settings of endemicity, but it plays an important role in areas of dengue emergence. This study compared the susceptibility of these 2 species to DENV infection by performing 232 direct blood-feeding experiments on 118 viremic patients with dengue in Vietnam. Field-derived A. albopictus acquired DENV infections as readily as A. aegypti after blood feeding. Once infected, A. albopictus permitted higher concentrations of DENV RNA to accumulate in abdominal tissues, compared with A. aegypti. However, the odds of A. albopictus having infectious saliva were lower than the odds observed for A. aegypti (odds ratio, 0.70; 95% confidence interval, .52-.93). These results quantitate the susceptibility of A. albopictus to DENV infection and will assist parameterization of models for predicting disease risk in settings where A. albopictus is present.